Current clinical immunotherapeutic approaches for head and neck cancer - Soto Chervin, Carolina (F1000Res, 2016)
It was estimated that 59,340 new cases of head and neck cancer would be diagnosed in the US alone in 2015 and that 12,290 deaths would be attributed to the disease. Local and regional recurrences may be treated with chemotherapy and radiation; however, metastatic head and neck cancer is fatal and is treated with chemotherapy for palliation. Recent successful treatment of a variety of solid and hematological malignancies by immunotherapeutic approaches (i.e. harnessing the body’s own immune system to combat disease) has added a fourth therapeutic option for the treatment of cancer. This commentary will review the status of immunotherapies in clinical development for the specific treatment of head and neck cancer.